Managing Bevacizumab-Related Gastrointestinal Perforation In Hepatocellular Carcinoma (HCC) Patients: A Systematic Review (The Review of Diabetic Studies, 2025)
Background:Bevacizumab, a monoclonal antibody targeting vascular endothelial growth factor (VEGF), is integral to first-line therapy for unresectable hepatocellular carcinoma (HCC) when combined with atezolizumab. However, gastrointestinal (GI) perforation, a rare yet life-threatening toxicity, has emerged as a significant clinical concern.Objective:This systematic review synthesizes current evidence on the incidence, mechanisms, risk factors, and management of bevacizumab-related GI perforation in HCC patients.Methods:Following PRISMA 2020 guidelines, ten peer-reviewed studies—including randomized controlled trials, real-world cohorts, and case reports—were analyzed. Data were extracted on patient demographics, treatment regimens, incidence of GI perforation, contributing factors, and survival outcomes.Results:Across included studies, the incidence of bevacizumab-induced GI perforation ranged from 0.5% to 2%, with fatality rates approaching 25–33%. Identified risk factors included portal vein thrombosis, cirrhosis (ALBI ≥ 2), and prior abdominal interventions. Despite these risks, atezolizumab-bevacizumab demonstrated superior overall survival (median 15–21 months) and disease control rates over sorafenib and lenvatinib. Multidisciplinary management—combining cessation of bevacizumab, prompt surgical or conservative intervention, and supportive therapy—improved survival outcomes.Conclusions:Bevacizumab-associated GI perforation remains rare but clinically significant in HCC management. Early detection, risk stratification, and careful monitoring can mitigate fatal complications while maintaining therapeutic efficacy.